Nodular fasciitis occurring at the anterior abdominal wall in a 12-year-old female - Tamotsu Kobayashi; Yutaka Kanamori; Mai Kutsukake; Masataka Takahashi; Motohiro Kano; Teizaburo Mori; Satoko Yamagishi; Ryoya Furugane; Akihiro Fujino; Takumi Shiobara; Yoshiyuki Tsutsumi; Osamu Miyazaki; et al. (Elsevier, 2021)
Nodular fasciitis occurring at the anterior abdominal wall in a 12-year-old female is reported. Nodular fasciitis has recently been recognized as a kind of neoplasm and its characteristic fusion genes such as MYH9-USP6 have been reported. The mass reported here occurred in a pediatric patient and the mass originated at the abdominal wall, whose clinical features were extremely rare.